Mechanisms of glacial‐to‐future atmospheric CO2 effects on plant immunity. Issue 2 (9th February 2018) - Williams, Alex; Pétriacq, Pierre; Schwarzenbacher, Roland E.; Beerling, David J.; Ton, Jurriaan
Summary: The impacts of rising atmospheric CO2 concentrations on plant disease have received increasing attention, but with little consensus emerging on the direct mechanisms by which CO2 shapes plant immunity. Furthermore, the impact of sub‐ambient CO2 concentrations, which plants have experienced repeatedly over the past 800 000 yr, has been largely overlooked. A combination of gene expression analysis, phenotypic characterisation of mutants and mass spectrometry‐based metabolic profiling was used to determine development‐independent effects of sub‐ambient CO2 ( sa CO2 ) and elevated CO2 ( e CO2 ) on Arabidopsis immunity. Resistance to the necrotrophic Plectosphaerella cucumerina ( Pc ) was repressed at sa CO2 and enhanced at e CO2 . This CO2 ‐dependent resistance was associated with priming of jasmonic acid (JA)‐dependent gene expression and required intact JA biosynthesis and signalling. Resistance to the biotrophic oomycete Hyaloperonospora arabidopsidis ( Hpa ) increased at both e CO2 and sa CO2 . Although e CO2 primed salicylic acid (SA)‐dependent gene expression, mutations affecting SA signalling only partially suppressed Hpa resistance at e CO2, suggesting additional mechanisms are involved. Induced production of intracellular reactive oxygen species (ROS) at sa CO2 corresponded to a loss of resistance in glycolate oxidase mutants and increased transcription of the peroxisomal catalase gene CAT2, unveiling a mechanism by which photorespiration‐derived ROS determined Hpa resistance at sa CO2 . By separating indirect developmental impacts from direct immunological effects, we uncover distinct mechanisms by which CO2 shapes plant immunity and discuss their evolutionary significance.